Morphotropic phase boundary and electrical properties of lead-free bismuth sodium lanthanum titanate-barium titanate ceramics - K. Pengpat (2018)
The important properties of lead-free piezoelectric ceramics have been investigated from Bismuth Sodium Lanthanum Titanate and Barium Titanate system: (1 - y)(Bi0.5Na0.5)(1 - 1.5x)LaxTiO3(BNLT)-yBaTiO3(BT) where x = 0.017 and y = 0 - 0.2, respectively. The morphotropic phase boundary (MPB) was found to be around y = 0.1 by the x-ray diffraction and dielectric measurement at various amount of BT. The temperature dependence of dielectric constant (εr) at various value of y showed the diffuse phase transition exhibiting the relaxor type ferroelectrics. The degree of diffuseness increased at a high doping content of about y = 0.15 where the second phase transition (T2) of the ferroelectric to antiferroelectric phase disappeared. Moreover, this sample had the maximum piezoelectric coefficient (d33) of about 112 pC/N with relatively low dielectric constant. The optimum sintering temperatures and the microstructures of the dense BNLT-BT ceramics were also examined. © Springer Science + Business Media, LLC 2006.